A Means to Alleviate the Bushmeat Crisis? The Feasibility of Establishing Sustainable Grasscutter Farms in Kenya - Menz, Alyssa (Consilience, 2015)
In Africa, the unsustainable, illegal hunting of wild animals for food, commonly referred to as the bushmeat crisis, causes multiple problems for ecosystems and human health. Given the lack of management of bushmeat hunting and rapidly expanding human population densities, the potential for overharvesting, driving populations of native species to local extinction, is of major concern unless effective and feasible alternatives can be developed. The farming of desirable native species offers one solution to reducing the demand for bushmeat, but farms must be economically viable, environmentally sustainable, and socially acceptable. This research uses Geographic Information Systems to examine the feasibility of establishing large native rodent (Thyronomys swinderianus) farms in Kenya. Given their high protein content, these rodents, commonly known as grasscutters, are a highly sought bushmeat species and have been successfully farmed in West and Central Africa. I performed an extensive literature review and consulted with grasscutter and sustainable livestock farm experts located in sub-Saharan Africa to determine physical and socio-political geographic factors most likely to constrain the development of sustainable grasscutter farms in Kenya, before using ArcGIS to map these criteria and a weighted overlay analysis to identify potentially favorable locations for establishing future farms. These maps identified three suitable geographic locations: the Western and Nyanza provinces; the Central province; and the southeastern tip of the Coastal province. The majority of Kenya reflects moderately suitable locations that are feasible for establishment as grasscutters are adaptive, low-intensity livestock, and previous studies have identified some of these moderately suitable locations as accepted livestock centers. These results are encouraging for the implementation of sustainable grasscutter farming in Kenya and the diversification of protein sources and economic development opportunities for rural dwellers. While the maps created are specific to Kenya, the methodology developed in this study is useful to global stakeholders attempting to alleviate the bushmeat crisis, combat food insecurity in a sustainable manner, and/or provide means of economic development to developing countries.